Sustainable Economic Development and Environmental Performance of Developing and Developed Countries - TAN, Chee Leong; ONG, Tze San; SOH, Wei Ni; RAHIM, Norhuda ABDUL (Journal of Environmental Management and Tourism; Vol 12 No 2 (2021): JEMT Volume XII Issue 2(50) Spring 2021DO - 10.14505//jemt.12.2(50).11, 2021)
At present, many economies are suffering from environmental problems that have significant effects on the climate and life of human beings, thus, the governments and institutions work to reduce the industrial negative effects on the environment.  Past studies focus on the nexus of sustainable economic development (SED) and environmental performance (EP) at the company or institution level. This study focused on the country level, and also further examined the outcome in developing and developed countries. This study examines the nexus between sustainable economic development and environmental performance of both developed and developing countries. The data of SED obtained from World Bank and Environmental Performance Index (EPI) for the period 2006-2016. This study also takes into consideration the control variable (CV) of primary school enrolment (SCH) and country population (POP), which may potentially influence the outcome of this study. For the analysis, the study employs panel regression model. The findings revealed that most of the proxies of SED have significant relationship with EPI.